INTERRELIGIOUS COUNCIL IN BOSNIA AND HERZEGOVINA - INTERRELIGIOUS DIALOGUE AND MEDIA-MEDIATED REALITY (Религиски дијалог и соработка, 2024)
In BiH, in 1997, a year after the constitution of the state on the basis of the Dayton Agreementand the end of the civil war, the Interreligious Council was formed on the initiative of religiousleaders and it was the first one under that name in the world. The path to reconciliation amongpeople and development of a stable society in BiH should lead through interreligious dialogue, andthe Interreligious Council strives to achieve that goal, in areas where the influence of churches andreligious communities is inviolable. The area of indisputable influence of the Interreligious Councilshould be sacred objects within which specific communication takes place between religiousleaders and believers. In that space, thoughts and views were expressed by members of the IslamicCommunity in BiH, imam Amir Mahić and theologian Muharem Štulanović. After the prayers in themosques, imams called the Serbian Orthodox Church a sect, its first enlightener, Saint Sava, theoriginator of fascism, with derogatory terms about the Serbian people. The public was informedabout the events in the mosques in Kozarac and Bihać through the media, with different narratives,while the Interreligious Council failed to represent the proclaimed goals and ideas of interreligiousdialogue. After more than two and a half decades of existence, there is no representative ofthe Serbian Orthodox Church in the Interreligious Council in BiH, because Metropolitan Bishop ofDabar-Bosna Hrizostom resigned from the Council, and the interreligious dialogue died down. Thestatements and analyzes presented in this paper are based on data obtained from research conductedthrough in-depth interviews with members of the Interreligious Council in BiH, analysis ofthe content of texts published in the media about the aforementioned cases in January 2023, andcomparative analysis, with the aim of elucidating the possibility of reviving interreligious dialogue,mutual understanding and the role of the media in those processes.